The essential transformation: How Masters students make sense and learn through transformative change. Issue 2 (April 2013) - Conklin, James; Kyle, Terry; Robertson, Colin
This article considers how the Human Systems Intervention Masters program at Concordia University in Montreal encourages and manages a transformation in the way students think about and act in the social world. The article explains the transformation in terms of a shift from a positivist/rational to a constructivist/narrative view of social phenomena, and how specific elements of the curriculum provoke the shift toward a more reflexive and participative way of working. The article also discusses the disconfirmation and uncertainty that can accompany the transformation, describes the structures and processes used to construct a container that provides psychological safety and emotional support for students, and considers ways in which the program might be improved.